Diversidad, Composición Y Estructura De Los Sistemas De Producción Agrícolas De Las Comunidades Shuar De La Amazonía Del Ecuador - Saavedra, Hilter Figueroa; Gaibor, Isabel Domínguez (European Scientific Journal, ESJ, 2018)
A diagnosis was applied on agricultural crops in the Shuar Yandia Yacu and San José de Armenia communities, in Orellana (Ecuador). Fourteen farms were chosen, seven in San José de Armenia and seven in Yandia Yacu. For sampling, they were divided into plots of 1x1 m for herbaceous and minor cultivable species, 5x5 m for shrubs and arable species of medium size, and 10x10 m for bigger cultivable and usable tree species. Data about composition and plant abundance were taken, by direct counting and participatory techniques, such as surveys and interviews. It was identified and classified by crop group, annual, perennial, use and utilitarian value. Indices of richness, diversity, similarity and cumulative frequency of the crops were calculated. As a result were found 97 agricultural species, the most representative families were Arecaceae, Solanaceae and Fabaceae, mostly fruit trees. The diversity and specific richness was registered low, representing approximately 5% of the registered agricultural species in the country. The annual food species with the highest accumulated frequency was corn (Zea maize L.), the perennial species of mayor importance was coffee (Coffea arabica L.), and the most important annual ancestral species was yucca (Manihotesculenta Crantz.). In conclusion there is a significant increase of monocultures, therefore it is necessary to recover and strengthen the production of ancestral crops to conserve the diversity of agricultural species in the Amazon region.